Money, the market, and the state : economic essays in honor of James Muir Waller - Waller, James Muir.; Beadles, Nicholas A.; Drewry, L. Aubrey (Athens, University of Georgia Press, 1968)
This book is the contribution of many scholars in the field of economics. The topics are grouped into two parts namely: Money and the state and the market and the state. In the first parts the authors x-rays the theorist of money in relation to state. While the second part deals with the activities of money market and the state.
Includes bibliographical references.
usc 20/6/17
Loans
Keywords: Waller, James Muir; Monetary policy; Economic policy